Pheochromocytoma in pregnancy – a rare but dangerous diagnosis - Romana Marušić; Marija Olujić; Tatjana Bačun (Medicinski glasnik, 2022)
Pheochromocytoma is a rare cause of hypertension in pregnancy. Unrecognized, it carries a great risk for both mother and the foetus. The main reason for missing the diagnosis is the misconception that any hypertension occurring in pregnancy is gestational hypertension or pre (eclampsia). As many as 90% of patients report one or more pheochromocytoma-related symptoms antenatally, but the diagnosis is made in 75% of patients, meaning that 3 out of 10 patients are diagnosed after childbirth or post-mortem. The symptoms are similar to other more common causes of hypertension in pregnancy, which presents a major diagnostic challenge. The diagnosis is based on determination of metanephrines in plasma or 24-hour urine. Magnetic resonance imaging (MRI) and ultrasound (US) are used to localize the tumour. If the diagnosis is made before the 24th week of pregnancy, laparoscopic removal of the tumour in the second trimester is recommended. If diagnosed later, the tumour could be removed during or after delivery. Preoperative preparation with alpha blockers is required to stabilize blood pressure. The decision on the mode of delivery depends on several factors, so an experienced multidisciplinary team is needed to minimize maternal and foetal mortality.
Keywords: hypertension; pheochromocytoma; preeclampsia